An assessment of policy approaches adopted to deal with bastee settlements of Dhaka City in Bangladesh - Mohit, Mohammad Abdul (Centre for Environment-Behaviour Studies (cE-Bs) and University Publication Centre (UPENA), UiTM, 2012)
Dhaka is the capital city of Bangladesh and it has a population of 12 million. During the last three decades, while the city population grew over 7%, bastee (slum and squatter) population of the city grew from 1.0 million in 1990 to 3.4 million in 2005. Several policy approaches were adopted to deal with bastee settlements of Dhaka since 1975. These policies approaches were not very effective, because the scale of the problem is very large, which provides future challenges to deal with the bastee situation.